Improving Maize Yield Through Locally Organic Resources: A Community-Based Strategy in Kaleke Village, Central Sulawesi - Mhd Fiqry Iskandar; Ilham Idris; Muhammad Shafwan Syarif; Magdalena Teresia; Iis Paramita; Rinaldi P. Tandu (Universitas Serang Raya, 2026)
The utilization of locally available organic materials as liquid organic fertilizer (LOF) represents an eco-friendly biofertilizer alternative that supports sustainable agriculture and environmentally responsible farming practices. This community service program aimed to improve farmers’ knowledge and technical skills in producing and applying liquid organic fertilizer derived from local organic resources, including moringa leaves (Moringa oleifera), aged coconut water waste, a weed-based biostimulant (BIOSAKA), and photosynthetic bacteria (PSB)to promote plant growth and enhance maize production. The program was implemented using a two-way interactive learning approach that combined educational sessions and hands-on practice on the utilization of organic liquid fertilizer (LOF) in maize cultivation. The program's effectiveness was primarily evaluated based on farmers’ level of understanding after the training activities. Evaluation was conducted using a structured questionnaire administered at the end of the program, which assessed participants’ comprehension of LOF materials, production principles, and application methods. The collected responses were used to determine changes in participants’ knowledge and overall learning outcomes resulting from the program. The evaluation results revealed clear quantitative improvements in farmers’ knowledge, technical understanding, and readiness to adopt locally derived organic fertilizers. Prior to the intervention, only 10–30% of participants were familiar with the concepts, raw materials, and production methods of liquid organic fertilizer (LOF), photosynthetic bacteria (PSB), and BIOSAKA. Post-training assessments showed a substantial increase, with 87–100% of farmers demonstrating an understanding of production procedures and application methods. In addition, 85% of participants recognized the functional roles of PSB, LOF, and BIOSAKA in supporting maize growth and soil fertility, while 95% expressed willingness to apply these organic inputs in their future farming practices. These quantitative shifts indicate that the community-based training effectively strengthened farmers’ capacity and confidence to utilize locally sourced organic resources independently.